2014
DOI: 10.1093/jac/dku300
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in bone mineral density after switching from tenofovir to abacavir in HIV-1-infected patients with low bone mineral density: two-centre randomized pilot study (OsteoTDF study)

Abstract: Switching from tenofovir to abacavir led to a slight improvement in femoral BMD although no differences were detected between groups. Larger studies are necessary before firm recommendations can be made on the discontinuation of tenofovir in patients with a low BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
1
35
1
Order By: Relevance
“…The largest of these trials [5] showed that, in addition to limb fat gains, switching to ABC had no significant effect on HIV-1 RNA, fasting lipids or glucose after 24 weeks. Other randomized studies [24,28,29] Low bone mineral density (BMD) has been reported in studies of HIV-infected individuals [37,38]. In a meta-analysis, the prevalence of osteoporosis was 3 times higher in HIVinfected patients than HIV-uninfected control subjects [38].…”
Section: Toxicity Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…The largest of these trials [5] showed that, in addition to limb fat gains, switching to ABC had no significant effect on HIV-1 RNA, fasting lipids or glucose after 24 weeks. Other randomized studies [24,28,29] Low bone mineral density (BMD) has been reported in studies of HIV-infected individuals [37,38]. In a meta-analysis, the prevalence of osteoporosis was 3 times higher in HIVinfected patients than HIV-uninfected control subjects [38].…”
Section: Toxicity Issuesmentioning
confidence: 99%
“…In a meta-analysis, the prevalence of osteoporosis was 3 times higher in HIVinfected patients than HIV-uninfected control subjects [38]. Both virological and immunological factors contribute to decreased BMD in HIV-infected patients [37][38][39].…”
Section: Toxicity Issuesmentioning
confidence: 99%
See 3 more Smart Citations